2021
DOI: 10.1111/fcp.12712
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressants with anti‐tumor potential in treating glioblastoma: A narrative review

Abstract: Glioblastoma multiforme (GBM) is known as the deadliest form of brain tumor. In addition, its high treatment resistance, heterogeneity, and invasiveness make it one of the most challenging tumors. Depression is a common psychological disorder among patients with cancer, especially GBM. Due to the high occurrence rates of depression in GBM patients and the overlap of molecular and cellular mechanisms involved in the pathogenesis of these diseases, finding antidepressants with antitumor effects could be consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 128 publications
0
8
0
Order By: Relevance
“…It possesses a good safety profile and optimal PK characteristics for CNS penetration [ 155 , 156 ]. Preclinical studies in various types of cancer have shown that fluoxetine induces its anticancer effect by inhibiting the NF-κβ signaling and inducing Ca 2+ related apoptosis [ 156 , 157 , 158 ]. Furthermore, fluoxetine has been found to act synergistically with temozolomide against glioma cells [ 154 , 159 ].…”
Section: Drug Repurposing For Glioblastomamentioning
confidence: 99%
“…It possesses a good safety profile and optimal PK characteristics for CNS penetration [ 155 , 156 ]. Preclinical studies in various types of cancer have shown that fluoxetine induces its anticancer effect by inhibiting the NF-κβ signaling and inducing Ca 2+ related apoptosis [ 156 , 157 , 158 ]. Furthermore, fluoxetine has been found to act synergistically with temozolomide against glioma cells [ 154 , 159 ].…”
Section: Drug Repurposing For Glioblastomamentioning
confidence: 99%
“…In turn, interleukin-6 contributes to supporting GBM progression via the autocrine pathway [ 206 ]. Generally, targeting 5-HT receptors is a type of potential way of treating GBM, functioning as reinforcement to chemotherapy [ 207 , 208 , 209 ].…”
Section: The Influence Of Neurotransmitters On Gbm and Potential Ther...mentioning
confidence: 99%
“…Following studies discovered that SSRIs suppress GBM cell proliferation in different ways. What is worth mentioning is that some FDA-approved antidepressants already reached favorable outcomes in clinical trials [ 208 , 210 ]. Considered as a more superior SSRI, escitalopram oxalate exhibits favorable tolerability.…”
Section: The Influence Of Neurotransmitters On Gbm and Potential Ther...mentioning
confidence: 99%
“…In fact, several in vitro and preclinical studies and reviews have evaluated the effect of antidepressants in tumors of the central nervous system. The review by Abadi et al suggested that the high occurrence rates of depression in glioblastoma multiforme patients, as well as the overlap of molecular and cellular mechanisms involved in the pathogenesis of these diseases, make antidepressants with antitumor effects an affordable strategy for the treatment of this tumor [93]. Some of the in vitro and preclinical studies go back to the end of the twentieth century, with the one reported by Richelson in 1978 being the earliest.…”
Section: Cancer Of Central Nervous Systemmentioning
confidence: 99%